Comunity Based Development and Infrastructure in Timor-Leste : Past Experiences and Future Opportunities - World Bank (Washington, DC, 2013)
This paper examines the opportunities, challenges and constraints of undertaking community-based development (CBD) programming in Timor-Leste, particularly through the lens of community-based provision of economically productive infrastructure. During an extended period of weak central governance in the aftermath of Timor Leste s turbulent independence struggle, external actors mainly foreign donor agencies and international NGOs broadly favoring a community-based approach played a dominant role in the country s reconstruction. In light of Timor Leste s political history and geographic isolation, it is not surprising that weak social capital and logistical obstacles have hampered CBD efforts, leaving Timor Leste with a mixed track record of success. Based on a longitudinal stock taking of CBD projects and face-to-face interviews with key actors in government, NGOs and the donor community, three specific initiatives are examined in detail with a view to elucidating key successes, constraints and opportunities as well as lessons learned that can inform the shifting policy environment.